Level of Youth Knowledge about Exclusive Breastfeeding in Karangjati Urban Village, Blora - Dewi Pamungkas; Novita Ika Wardani (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2019)
Exclusive breastfeeding is breast milk which gives to infants during the first 6 months without any additional drink or food. The Ministry of Health of Indonesia Republic targeted that the scope of exclusive breastfeeding for infants less than 6 months in 2016 by 54.0%. The efforts to increase exclusive breastfeeding coverage by improving knowledge about breast milk in early childhood. The purpose of this study is to determine the knowledge level of adolescent about breastfeeding eduaction by using Dukesi media (Module Packet of ASI). Teenagers who are members of youth and youth groups can join in “teenegers who care about exclusive breastfeeding”. The task of this group is to assist the campaign for exclusive breastfeeding to become successfull and hopefully being the successor for the next generation. This study is comparative analytic by dividing the adolescent into two groups. Total Sampling technique is the method for sampling on 68 female adolescents. Data Questionnaires are used to collect the data. The results of Mann Whitney test have an influence with the knowledge level on adolescent about breast milk. The counseling between intervention group and control group showing significant differences that is P = 0,000 or significanctly P 0,005. The conclusion of this research is the use of Dukesi media has infulenced teenagers about the knowledge level of breast milk in Karangjati Village Blora regency.